Hukum Pemaksaan Seksual Dalam Berhubungan Suami-Istri - Muhammad Haikal (Institut Agama Islam Al-Aziziyah Samalanga, 2022)
This study aims to find the law of coercion of husbands against wives in fulfilling their needs. This type of research is a library by analyzing fiqh and the opinion of scholars. Sources of data obtained from various kinds of fiqh fiqh. The data analysis technique is descriptive analysis using inductive patterns. The results of the study show that the law of sexual coercion of husbands on wives according to the views of the syāfi'iyyah scholars with the details is permissible if the coercion does not occur mani' and old syar'i. Makruh if a wife is pregnant and has the potential to damage the pregnancy and unlawful if it is confirmed to damage the pregnancy. Coercion committed by a husband against his wife in the perspective of Islamic law, if the coercion is justified by syara', then the coercion of the husband is not considered a crime.